Rise of Jonas Olsen : a Norwegian Immigrant?s Saga. - Wist, Johannes B. (University of Minnesota Press, 2005)
The Rise of Jonas Olsen is at once an immigrant novel, business novel, political novel, and a western, offering a rich and panoramic view of Scandinavian immigrant life in the Upper Midwest. Johannes B. Wist combines realism and satire to depict the role Norwegian Americans played in the economic, political, and cultural life of the Upper Midwest.